1997
DOI: 10.1111/j.1471-0528.1997.tb11542.x
|View full text |Cite
|
Sign up to set email alerts
|

The levonorgestrel intrauterine system in the management of menorrhagia

Abstract: Objective To assess the effect of a levonorgestrel releasing intrauterine system in the management of Design A prospective study.Setting A district general hospital in South Wales.Methods Fifty women with a failed trial of medical therapy and awaiting hysterectomy or transcervical resection of the endometrium (TCRE) were treated with a levonorgestrel intrauterine system. The menstrual loss was estimated using a modified pictorial chart together with a full blood count and ferritin measurement preinsertion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
2
7

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(69 citation statements)
references
References 9 publications
4
55
2
7
Order By: Relevance
“…In our study, the women reported an improvement in their symptoms of premenstrual tension. The reason for this improvement is difficult to understand as the amount of levonorgestrel entering the circulation is low but a similar improvement was reported in the earlier phase of the study 3 .…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…In our study, the women reported an improvement in their symptoms of premenstrual tension. The reason for this improvement is difficult to understand as the amount of levonorgestrel entering the circulation is low but a similar improvement was reported in the earlier phase of the study 3 .…”
Section: Discussionmentioning
confidence: 75%
“…They were offered and accepted the LNG-IUS (Mirena: Schering Healthcare, UK ). All 50 women were sent a questionnaire including a pictorial menstrual chart at three months and after one year and these results have been published 3 . In this long term follow up study, the women were asked for information on their continued use of the LNG-IUS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve percent of patients with a Mirena IUS in situ report no change in symptoms [10]. One disadvantage of the Mirena IUS is the erratic vaginal bleeding that may occur in the early months of its use.…”
Section: Discussionmentioning
confidence: 99%
“…Although there was a higher rate of successful treatment in those undergoing transcervical resection or balloon ablation in four trials, rates of satisfaction and change in quality of life were similar, but women with levonorgestrel-releasing intrauterine system had a greater incidence of progestogenic side effects within a year. In two studies, 82% and 64% of women on a waiting list of hysterectomy cancelled their surgery after using levonorgestrel-releasing intrauterine system (Barrington & Bowen-Simpkins, 1997;Lähteenmaki et al, 1998). Another study comparing levonorgestrel-releasing intrauterine system with hysterectomy, revealed that there was no significant difference in quality of life scores, but the former treatment had lower costs than the latter (Hurskainen et al, 2001).…”
Section: Levonorgestrel-releasing Intrauterine Systemmentioning
confidence: 99%